Targeting School Feeding Programs at Vulnerable Sub-Groups - International Food Policy Research Institute (International Food Policy Research Institute, 2010)
This complex evaluation of a large-scale program uses a cluster-randomized design where 20 geographic clusters (subdistricts) were randomized to study two sets of interventions. For the evaluation of behavior change interventions only, the 20 clusters were randomized to 10 intensive and 10 non-intensive interventions areas. For a sub-study to evaluate a market-based model for delivering micronutrient powders (MNP) along with behavior change interventions, there was subsequent randomization to comparison area, MNP-only area, Behavior Change Communication (BCC)-only area and MNP+BCC areas.